Analisis Legalitas Pembatasan Impor Produk Pangan Berdasarkan Alasan Kesehatan Publik dalam Kerangka WTO - Fatimah Azzahra (Media Hukum Indonesia (MHI), 2026)
This study analyzes the legality of restrictions on food imports based on public health grounds within the legal framework of the World Trade Organization (WTO), specifically through the provisions of the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS Agreement). The tension between a country's sovereign right to protect the health of its citizens and its obligation to liberalize trade often causes controversy, especially when health standards are used as the basis for imposing non-tariff barriers that are potentially protectionist in nature. Using a normative legal research method, this study examines the SPS legal framework, relevant WTO dispute rulings including cases DS484 and DS477/DS478, and academic literature from the last five years. The results show that WTO legal standards require health-based measures to comply with the fundamental principles of scientific basis, proportionality, and non-discrimination, in addition to transparency obligations. The WTO's discrimination assessment mechanism is comprehensive, involving substantive and administrative evaluations, including an examination of the impact of policies on imported products and the consistency of their implementation. This study concludes that Indonesia's main challenges lie in the overlap between health and economic protection objectives, the lack of risk assessment capacity, and administrative inconsistencies that could trigger international disputes. This research is expected to contribute academically to the development of international trade law studies and offer practical guidance for policymakers in designing food regulations that are legally valid, proportional, and in accordance with WTO standards..